2022
DOI: 10.3390/su14073775
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the Cooling Loads of Buildings Using Shading Devices: A Case Study in Darwin

Abstract: It is estimated that almost 40% of the world’s energy is consumed by buildings’ heating, ventilation, and air conditioning systems. This consumption increases by 3% every year and will reach 70% by 2050 due to rapid urbanisation and population growth. In Darwin, building energy consumption is even higher and accounts for up to 55% due to the hot and humid weather conditions. Singapore has the same weather conditions but less energy consumption, with only 38% compared to Darwin. Solar radiation can be defined a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 57 publications
0
7
0
1
Order By: Relevance
“…This is consistent with the findings of a study [43], which indicated that shading can be minimized by choosing the best location for solar panel installation. Additionally, solar PV arrays can themselves be used as shading devices, thus reducing direct solar heat gain by homes (while having unimpeded exposure to sunlight for power generation) and thus reducing the latent energy demand required for cooling [44].…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the findings of a study [43], which indicated that shading can be minimized by choosing the best location for solar panel installation. Additionally, solar PV arrays can themselves be used as shading devices, thus reducing direct solar heat gain by homes (while having unimpeded exposure to sunlight for power generation) and thus reducing the latent energy demand required for cooling [44].…”
Section: Discussionmentioning
confidence: 99%
“…By using a comprehensive approach, they managed to reduce the annual final energy consumption for cooling by 70%. Mohammed et al installed seven types of shading devices on the Darwin town hall building (Australia) and achieved savings of 15.5% [38].…”
Section: Figure 1 Interaction Between Eeb and Ber In Serbiamentioning
confidence: 99%
“…Therefore, shadings affect how much energy is used for lighting, heating, and cooling a structure, as well as its occupants' visual and thermal comfort (Xu et al, 2022). The wall surfaces that receive the shading devices might be internal or external (Mohammed et al, 2022). Moreover, external shading devices such as canopies, awnings, horizontal louvers, and overhangs are preferred over internal ones because they are more effective at reducing solar gains by preventing excessive heat from entering the building space.…”
Section: Introductionmentioning
confidence: 99%